Pengaruh Gaya Kepemimpinan, Insentif Dan Disiplin Kerja Terhadap Kinerja Karyawan ( Studi Kasus Pada PT. Misaja Mitra Pati ) - Mohamad Yonanda Alvereza; N. Rachma; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to determine the effect of leadership style, incentives and work discipline on employee performance. The object of this research is PT. Misaja Mitra Pati with a sample of 88 respondents with a record of active employees and workers at the PT. The sampling technique used was purposive sampling. Data collection techniques using questionnaires and data analysis tools. Testing the data used is simultaneous hypothesis testing (F) and partial hypothesis testing (t). The results showed that simultaneously the independent variables had a significant effect on the dependent variable. Based on the partial test results, the variables of leadership style, incentives and work discipline have a significant effect on employee performance at PT. Misaja Mitra Pati.  Keywords: Leadership Style, Incentives, Work Discipline And Employee Performance